Construction and optimization of a nisin-controlled expression vector using a pre-screened strong promoter in Streptococcus thermophilus - Ye, Yanxin; Zhao, Ruiting; Li, Leilei; Li, Zhi; Chen, Yanyan; Xu, Zhenshang (Frontiers in Microbiology, 2025)
The nisin-controlled gene expression (NICE) system is an efficient and promising gene expression system for Lactococcus lactis. To enhance the expression efficiency of the NICE system in Streptococcus thermophilus ATCC19258, an inducible expression vector, pNZ8148-PnisA-gfp-PnisR-nisR-nisK, containing the regulatory element NisR/K and the promoter PnisR, was first constructed using the basic plasmid pNZ8148. Green fluorescent protein (GFP), as the reporter protein, was cloned downstream of PnisA in the vector pNZ8148 to detect protein expression. The resulting expression vector was electroporated into S. thermophilus, Lactobacillus plantarum, and Enterococcus faecium, demonstrating that the NICE system can be used to induce protein production in various hosts of lactic acid bacteria. The optimal conditions for protein expression of the recombinant strain S. thermophilus/pNZ8148-PnisA-gfp-PnisR-nisR-nisK also showed that the expression level was the highest when the optimal induction concentration of nisin was 2,500 ng/mL for 3 h after induction. The recombinant plasmid pNZ8148-PnisA-gfp-PnisR-nisR-nisK was optimized using a strong promoter (P15, P18, P23, or P25) pre-screened from S. thermophilus instead of the native promoter PnisR. The results indicated that when the derived plasmid pNZ8148-PnisA-gfp-P25-nisR-nisK was electroporated into S. thermophilus, the resulting recombinant strain S. thermophilus/pNZ8148-PnisA-gfp-P25-nisR-nisK exhibited the highest expression level of heterologous green fluorescent protein. These results suggest that the improved plasmid-based nisin-controlled expression system has the potential to be used for desired protein production in S. thermophilus.